Primary care dentistry: Past, present and future. - Rand Hamad AlMujel, Alanood Abdulkarim Alzuhair, Amal Hamad AlShubeki, Lamia Shafi ALDossari, Seetah Alajmi, Abrar Mohammed Aljanadi, and Nouf Saud Almunaiseer (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Oral health is vital to overall well-being, yet dental diseases are among the most neglected chronic conditions. This paper examines the past, present and future of primary care dentistry. It provides a historical background of primary care dentistry and describes stages of its evolution. Historically, dentistry has transitioned from basic practices in ancient civilizations to a focus on preventive care and public health. In Saudi Arabia, primary care dentistry now employs a multidisciplinary team approach, emphasizing early disease detection and health promotion, supported by digital technologies and evidence-based practices.